Merepresentasikan Makna dalam Lagu “Nusantara 1” Karya Koes - Raisya Putra Pratama; Elsa Melinda (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
Nusantara song 1 (one) is one of several koes plus songs with an archipelago (Indonesia) theme. The objectives of this study include (1) to reveal the meaning contained in the lyrics of the song Nusantara 1 (one) by Koes Plus, (2) to describe the representation of nationalism contained in the lyrics of the song Nusantara 1 (one) by Koes Plus, (3) what figurative language which is contained in the 1 (one) archipelago song by Koes Plus. The problem contained in representing this 1 (one) archipelago song is that the lyrics of this song tell about the beauty of the archipelago (Indonesia) and contain an invitation to people to unite with each other and mutually protect the integrity of the archipelago (Indonesia), but many are represented as lyrics. songs that lead to something that smells of romance, so many people misinterpret the lyrics of the song, making it a complex matter to be discussed in this study. With a different meaning of the lyrics of the archipelago 1 (one) song regarding the reality of the original lyrics made by the creator. Through research methods that are analytical descriptive by concluding data through literature study. Based on the results of the research, the views of the wider community regarding the 1 (one) archipelago song produced by Koes plus its meaning become clear and detailed, namely telling about the beauty of the archipelago which is packaged in poetic words that contain many meanings using association figures of speech.